The Measurement Model of Social Capital, Risk Taking, and Entrepreneurial Financing Choice in SMEs in West Sumatra - Ahmad, Faddilla; Masdupi, Erni (Financial Management Studies, 2024)
This study demonstrates the measurement model of Entrepreneurial Financing Choices, Social Capital, and Risk Taking of SMEs in West Sumatra in 2023, through (confirmatory factor analysis -- CFA). This study aims to test the accuracy of the measurement model with the data collected, with a large sample of 338 respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) method using IBM SPSS Amos 24 software. SEM is also known as a two-step approach consisting of a measurement model test and also a structural model test. All indicators for each variable in this study have a loading factor value above 0,3 which indicates convergent validity is met. In the Entrepreneurial Financing Choice variable, the third indicator has the highest value of 0,962 and the first indicator has the lowest value of 0,435. In the Social Capital variable, the seventh indicator has the highest value of 0,858 and fourth indicator has lowest value of 0,395. In the Risk Taking variable, the second indicator has the highest value of 0,942 and the fifth indicator has the lowest value of 0,613.